An Electrochemical Aptamer-Based Biosensor for Rapid and Ultrasensitive Detection of Carbaryl by Red Blood Cell-Like Mofs - Tasca-Gottardo, F; Tasca-Gottardo, F (Elsevier B.V., 2025)
Carbaryl (CBA) is a broad-spectrum carbamate insecticide widely used to control pests on crops, trees, and ornamental plants. CBA residues in foods can accumulate in the human body and damage human health, making it challenging to develop a sensitive and reliable detection method. Herein, a spherical, red blood cell-like metal-organic frameworks (rbMOFs) has been proposed to overcome the limitations of the detection method, particularly in terms of sensitivity and selectivity. The spherical, rbMOFs with an appropriate ratio of reduced graphene oxide (rGO) as a new group of nanocomposites was used for detection of CBA by electrochemical aptasensor by using screen-printed red blood cell-like MOFs-reduced graphene oxide electrodes (SP-rbMOFs/rGO-E). The differential pulse voltammetry (DPV) showed that the linear range for CBA was 1.0 pmol L−1-0.1 µmol L−1 with limits of detection of 0.4 pmol L−1. The proposed electrochemical aptasensor exhibited good repeatability (RSD%=2.96), reproducibility (RSD%=3.14), and stability (92 %). In the CAB examination of tap water, apple juice, and potato juice, the suggested aptasensor demonstrates excellent selectivity, repeatability, stability, high efficiency, and acceptable recovery. Owing to its simplicity and portability, the method has the potential for on-site detection of CBA in various food samples. © 2025 The Authors